PENGGUNAAN MEDIA GAMBAR IDOLA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS X SMA NEGERI 1 BANTAENG - Abd. Rahman (Jurnal Pendidikan Sang Surya, 2021)
This research is a classroom action research which aims to improve speaking skills by using madia images of idols in class X SMA Negeri 1 Bantaeng. The research subjects were students of class X SMA Negeri 1 Bantaeng with a total of 25 students. This research was conducted in 2 cycles. The data from the observation of student activities were analyzed qualitatively. Student learning outcomes data were analyzed quantitatively using descriptive statistics. The results showed that the value of speaking skills using the idol image media in Class X SMA Negeri 1 Bantaeng increased. In the first cycle it is categorized as "moderate" with an average value of 67.73, then it increases in the second cycle with an average value of 70.00 which is also still categorized as "moderate". The results of observations of student activity increased by 1.67 percent, from the first cycle of meetings 1 and 2 on an average of 77.33 percent to 82 percent at meetings 3 and 1 in cycle II. Based on the results of this study, it can be concluded that there is an increase in speaking skills using the idol image media in class X SMA Negeri 1 Bantaeng.